From epigenetics to anti-doping application: a new tool of detection - Schiera, Gabriella; Contrò, Valentina; Sacco, Alessia; Macchiarella, Alessandra; Cieszczyk, Pawel; Proia, Patrizia (Human Movement, 2017)
Eukaryotic genomes transcribe up to 90% of the genomic DNA but only 1–2% of these transcripts encode for proteins, whereas the vast majority are transcribed as non-coding RNAs (ncRNAs). They are divided into short ncRNA, particularly microRNA (miRNA) and small interference RNA (siRNA), and long ncRNAs. Noteworthy, they are unexpectedly stable since they are protected from degradation through different mechanisms: package in exosomes/microvesicles structures, in apoptotic bodies, in HDL lipoprotein, or by RNA binding proteins. For several years already, biomarkers have been used to detect biological disease; in the last years, a requirement appeared to find some of them to unearth the signs of doping. The potential of ncRNAs as a biological candidate is strongly debated and it seems to have become the right tool in the anti-doping hands. In the recent years, the next-generation sequencing (NGS) technology was used by the World Anti-Doping Agency to draft the athlete biological passport (ABP), measuring the circulating miRNAs and applying these new biomarkers in anti-doping. NGS technology does not require any prior knowledge of ncRNAs, but the limit to employ this biomarker to detect performance-enhancing drug use must consider the intrinsic and extrinsic factors that might affect measurements.